PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VC SDN35 PETANI KECAMATAN MANDAU KABUPATEN BENGKALIS - Desmalina Desmalina; Hamizi Hamizi; Erlisnawati Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:The problem in this research is the student achievement of social studies fifth graderes (VC) SDN 35 Petani Kecamatan Mandau Kabupaten Bengkalis still low with an average value of 55,28 and minimum completenness criteria (KKM) social studies is 65.The purpose of this research was to improve the students achievement of the fifth graders (VC) SDN 35 Petani Kecamatan Mandau Kabupaten Bengkalis with the implementation cooperative learning type talking stick model. This research is Classroom action Research (CAR) with two cycles in second semester 2014/2015. Before implementation of cooperative learning type talking stick model, average from the base score 55,28. After implementation of cooperative learning type talking stick model, UH I was 67,4 that improve 12,12 % from before exam with average 55,28. UH II was 74,8 that improve 19,52 %. Teacher’s activities with the implementation of cooperative learning type talking stick model at first meeting of first cycle was 70,8 % (good category), and second meeting was 75 % (good category). At second cycle, teacher’s activities at first meeting was 87,5 % (good category) and second meeting was 95,83 % (best category). Students activities at first meeting of first cycle was 64,28 % (enough category) and second meeting was 75 % (good category). At second cycles, students activities at first meeting was 85,71(good category) and second meeting was 92,86 % (best category). Implementation cooperative learning type talking stick model can improved social studies students achievement of fifth graderes (VC) SDN 35 Petani Kecamatan Mandau Kabupaten Bengkalis.Key Words : Cooperative Type Talking Stick, Social Studies Student’s Achievement.